2025 AICCRA Zambia Annual Work Plan and Budget - Chinembiri, Evans; Kakwasha, Keagan (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
Building upon initial successes, AICCRA Zambia, led by the International Water Management Institute and partners, enters a pivotal phase in 2024-2025 with Additional Financing (AF). This phase amplifies transformative agricultural initiatives, emphasizing climate-smart agriculture (CSA) and climate information services (CIS), agripreneurship, and alignment with national objectives to bolster food security, climate resilience, and community prosperity.